2014
DOI: 10.1039/c4cp01846j
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared photocatalytic activity induced by intrinsic defects in Bi2MO6(M = W, Mo)

Abstract: The electronic structure and related photocatalytic properties of Bi2MO6 (M = W, Mo) with various intrinsic defects are studied based on the first-principles density functional theory (DFT). Our results indicate that O vacancies form easily in both Bi2WO6 and Bi2MoO6 under Bi rich/O poor conditions. The near-infrared light transitions can be realized involving electrons from the O vacancy induced impurity states within the band gap to the conduction band. Rather than acting as photogenerated carrier recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 34 publications
(38 reference statements)
7
50
0
Order By: Relevance
“…This illustrates the existence of g-C 3 N 4 in the 25%g-C 3 N 4 /Bi 2 MoO 6 composites. It could be seen that the absorption peak of 25%g-C 3 N 4 /Bi 2 MoO 6 at 668 cm -1 was ascribed to the Bi-O stretching mode [51]. The FT-IR and HRTEM results show that Bi 2 MoO 6 and g-C 3 N 4 have been coupled together successfully.…”
Section: Photocatalytic Experimentsmentioning
confidence: 86%
“…This illustrates the existence of g-C 3 N 4 in the 25%g-C 3 N 4 /Bi 2 MoO 6 composites. It could be seen that the absorption peak of 25%g-C 3 N 4 /Bi 2 MoO 6 at 668 cm -1 was ascribed to the Bi-O stretching mode [51]. The FT-IR and HRTEM results show that Bi 2 MoO 6 and g-C 3 N 4 have been coupled together successfully.…”
Section: Photocatalytic Experimentsmentioning
confidence: 86%
“…The oxygen vacancy induced impurity states are delocalized along (001) and (100) directions, but localized along the (010) plane, suggesting that the transfer of photogenerated holes is anisotropic. Due to the small effective mass and substantial dispersion of impurity states, the photogenerated holes can quickly transfer to the surface and enhance the reaction rates [243].…”
Section: Photocatalytic Activity Of Bi 2 Womentioning
confidence: 99%
“…Oxygenv acancy,a se lectron donor,c an also increase the electron density on the semiconductor photocatalyst. [15] The increased electrons can form ad onor level, narrow the energyg ap band, and extendt he absorption range. [16] Jing et al have calculated the impurity levelsi nB i 2 MO 6 (M = W, Mo) and the results revealed that the impurity states caused by oxygen vacancies favor the transfero fp hotogenerated holes and would furtherb enefit the photocatalytic process.…”
Section: Introductionmentioning
confidence: 99%